2020
DOI: 10.4067/s0718-58392020000100072
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between grain yield and agronomic traits of rice in southern China

Abstract: Field experiments were conducted to evaluate the grain yield and agronomic traits of inbred and hybrid rice (Oryza sativa L.) 'Yuxiangyouzhan' and 'Shenliangyou 58 xiangyouzhan' at 11 different planting sites during 2013-2017 in Southern China. The grain yield, growth period, panicle number m-2 , productive tiller percentage, plant height, panicle length, grain number per panicle, filled grain number per panicle, filled grain percentage, and grain weight were evaluated. Results indicated that 'Shenliangyou 58 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
(30 reference statements)
6
9
0
2
Order By: Relevance
“…The application of N as basal (B), Mid-tillering (MT), panicle initiation (PI) and late booting (LB) is necessary for optimum photosynthesis during growth stage to produce great number of filled grains as improve in sink size and capacity of rice. Similar results were obtained by Singh and Singh (1998); Luikhan et al, (2004) and Zhao et al, (2020). However there is no significant difference observed for 1000 grain weight under different split of nitrogen fertilizer.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The application of N as basal (B), Mid-tillering (MT), panicle initiation (PI) and late booting (LB) is necessary for optimum photosynthesis during growth stage to produce great number of filled grains as improve in sink size and capacity of rice. Similar results were obtained by Singh and Singh (1998); Luikhan et al, (2004) and Zhao et al, (2020). However there is no significant difference observed for 1000 grain weight under different split of nitrogen fertilizer.…”
Section: Resultssupporting
confidence: 87%
“…Applying nitrogen fertilizer at an appropriate dose and time helps to enhance the photosynthetic activity of rice plants, improve resistance to pests, improve dry matter accumulation, promote better nutrient absorption, and thereby increase grain yield (Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The yield capability could be achieved by selecting the number of panicles per plant and the weight of the panicle characters. This may be due to the fact that the yield potential was mainly attributed to the number of grains per panicle and panicle weight (Zhao et al, 2020b). All these components caused heavy weight of panicles and high yielding ability as well as a greater number of panicles plant −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a positive correlation of plant height and panicle length was also reported by Sohrabi et al (2012) and Lasalita-Zapico et al (2010) in upland rice, while Demewez et al (2014) reported a negative correlation between 1000grain weight to the days-to-50% heading and days-to-maturity, respectively. On the other hand, a positive correlation of plant height and yield among lowland rice was reported by Zhao et al (2020) whereas a negative correlation of days-tobooting and maturity with 1000-grain weight was recorded by Abraham et al (2017). A shorter vegetative growth may help to produce heavier grains, however this trait only contributes positively to the yield per plant of lowland rice varieties but not the yield of the upland rice varieties.…”
Section: Comparison Of Agronomic Traits Of Lowland and Upland Rice Vamentioning
confidence: 94%